RELATIONSHIP BETWEEN BUSINESS DEVELOPMENT SERVICES AND GROWTH OF SMALL AND MEDIUM ENTERPRISES IN KENYA - Mwaniki, Zipporah; Ngugi, Patrick; Nyang'au, Samson (European Journal of Business and Strategic Management, 2022)
Purpose: The purpose of this study was to find out the relationship between business development services and growth of small and medium enterprises in Kenya Methodology: The study adopted a descriptive survey design. The target population was 422 manufacturing SMEs in Nairobi County who are members of Kenya Association of Manufacturers. Nairobi County was purposively selected. Both stratified and simple random sampling was used to select a representative sample. Both primary and secondary data collection techniques were employed. A Pilot study was conducted on 20 manufacturing SMEs in Kiambu County to establish and improve on the validity and reliability of research instruments. Data collected was coded and stored in tabular form using Microsoft Excel. Data was analyzed using both quantitative and qualitative data analysis methods. Quantitative data was analyzed using Statistical Package for Social Sciences (SPSS) Version 25 software through descriptive statistics (measures of central tendency and measures of dispersion). Data was presented through Tables. Results: The study found out that there was a significant positive relationship between business development services and growth of small and medium enterprises in Kenya. According to the results of this study, 23% of growth of small and medium enterprises in Kenya is explained by business development services. Unique contribution to theory, practice and policy: The study recommended that policies should be formulated to strengthen public-private partnerships should be established and strengthened to nurture and support the overall entrepreneurial ecosystem in order to encourage greater growth among manufacturing SMEs, foster academia-industry collaborations for creation of new technologies and innovation in the existing technologies. Appreciate the local technologists and encourage local technology development by providing tax reliefs for preferred industries.